2014
DOI: 10.1111/ppl.12185
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to cavitation in Olea europaea current‐year shoots: further evidence of an open‐vessel artifact associated with centrifuge and air‐injection techniques

Abstract: Different methods have been devised to analyze vulnerability to cavitation of plants. Although a good agreement between them is usually found, some discrepancies have been reported when measuring samples from long-vesseled species. The aim of this study was to evaluate possible artifacts derived from different methods and sample sizes. Current-year shoot segments of mature olive trees (Olea europaea), a long-vesseled species, were used to generate vulnerability curves (VCs) by bench dehydration, pressure colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(137 citation statements)
references
References 44 publications
8
125
4
Order By: Relevance
“…Importantly, the iso-/anisohydric dichotomy does not account for differences in vulnerability to xylem embolism [12], nor for leaf traits involved in turgor regulation [65]. Given the current methodological controversy on the measurement of vulnerability to xylem embolism (e.g., [48,61]) we cannot be sure that the extremely high PLC values estimated here are real. However, several notes are in order: (i) extremely high (~80%) PLC is also predicted by more conservative vulnerability estimates under extreme drought ( Figures 8 and 9); (ii) extremely high PLC in the xylem is consistent with measured seasonal reductions in kS-L ( Figure 6); (iii) the relationship between ΨPD and ΨMD for this species (Figure 3) suggests a similar sensitivity of stomata and plant hydraulic conductance to declining water potential (cf.…”
Section: Contrasting Hydraulic Strategies In P Sylvestris and Q Ilexmentioning
confidence: 77%
See 1 more Smart Citation
“…Importantly, the iso-/anisohydric dichotomy does not account for differences in vulnerability to xylem embolism [12], nor for leaf traits involved in turgor regulation [65]. Given the current methodological controversy on the measurement of vulnerability to xylem embolism (e.g., [48,61]) we cannot be sure that the extremely high PLC values estimated here are real. However, several notes are in order: (i) extremely high (~80%) PLC is also predicted by more conservative vulnerability estimates under extreme drought ( Figures 8 and 9); (ii) extremely high PLC in the xylem is consistent with measured seasonal reductions in kS-L ( Figure 6); (iii) the relationship between ΨPD and ΨMD for this species (Figure 3) suggests a similar sensitivity of stomata and plant hydraulic conductance to declining water potential (cf.…”
Section: Contrasting Hydraulic Strategies In P Sylvestris and Q Ilexmentioning
confidence: 77%
“…Our PLC values were estimated from xylem vulnerability curves obtained using appropriate methods for each species-air injection for P. sylvestris and bench dehydration for Q. ilex [48,60]. However, none of these methods is free of potential artifacts [61], and estimated branch P50 values for Q. ilex in the study site (−2 MPa; [47]) are low compared to the range of values reported in other studies (between −3.8 and −6.6 MPa; [27,48,62,63]). If we use the vulnerability curves recently reported for a climatically similar Q. ilex population (−4.70 MPa; [48]) to estimate branch PLC, Q. ilex would keep PLC below ~20% except for the drought period in 2011, when PLC reached ~80% (Figure 8).…”
Section: Contrasting Hydraulic Strategies In P Sylvestris and Q Ilexmentioning
confidence: 99%
“…Alternatively, the relaxation procedure has been shown to introduce other potential errors related to rehydration-induced embolism refilling (Trifilo`et al 2014b). Recommendations for standardizing measurements of vulnerability curves have recently been described (Torres-Ruiz et al 2014). Future research should carefully evaluate the occurrence and magnitude of cutting or relaxation artefact in species investigated for their refilling capability.…”
Section: Methodsological Precautionsmentioning
confidence: 99%
“…However, recent publications have provided evidence that some measurement techniques used to evaluate the hydraulic function and vulnerability to cavitation of plant organs may be prone to artifacts (Sperry et al, 2012;Torres-Ruiz et al, 2014;Trifilò et al, 2014). The discovery of these artifacts has raised questions regarding the reliability of some previously published plant hydraulics data, in particular data relating to the refilling of embolized xylem conduits while the xylem is under tension.…”
mentioning
confidence: 94%